Tawang Volleyball Cup sebagai Ajang Pemersatu Masyarakat Desa Tawang - Nurfaizzatu Dzikrillah; Eliza Mutiara Nasywa; Martin Sudarmono (Universitas Negeri Semarang, 2026)
Tawang Volleyball Cup is an initiative by Giat 9 Students of Universitas Negeri Semarang aimed at strengthening social bonds and enhancing the sense of togetherness among the residents of Tawang Village through an inter-neighbourhood volleyball tournament. This event not only improves the technical and mental abilities of the players, but also applies the values of Pancasila, especially the third principle